Diseño de un prototipo para la instalación de tubería en montajes de red contraincendios con capacidad máxima de 600 kg - Perdomo Figueroa, Yesid Felipe (Universidad Antonio Nariño, 2022)
In this document an investigation is carried out on how to develop the activities of facilities for fire fighting systems that work using carbon steel pipe; the research focuses on that currently there are many solutions on the market that can be used or provide a very good alternative when performing the lifting of heavy loads for the anatomy of the human being. But in the market of fire fighting installations, especially when implementing carbon steel pipe which after exceeding two meters far exceeds the masses that by health should handle a human being there is no viable solution on the market for people engaged in these activities. That allows them to perform their work in a better way protecting their health and the integrity of their body while performing their activities.